Gut microflora and intestinal morphology of commercial broiler chickens and red jungle fowl fed diets containing palm kernel meal - Idrus, Zulkifli; Soesanto, Iman Rahayu Hidayati; Alimon, Abdul Razak; M. P. K. Menon, M. K. Vidyadaran; Babjee, Shaik Mohamed Amin (Verlag Eugen Ulmer, 2009)
From days 21 to 56, equal number of the commercial broilerchickens (CB) and the red jungle fowl (RJF) were fed diets containing either 0% palm kernel meal (Diet A) or 25% palm kernel meal (Diet B). On days 28 and 56, the number of microflora (Lactobacillus sp. and Streptococcus sp.) in the gut contents of ileum and caecum were taken from six randomly selected birds per sub-group. Same number of birds per genotype-regimen subgroup were used for the measurements of height and width of villi of the duodenum and ileum and, columns of the caecum samples.